Disentangling the relationship between race and attitudes toward the police: police contact, perceptions of safety, and procedural justice - Wheelock, Darren (Crime & delinquency, 2019)
Recent incidents involving police shootings of unarmed men of color have increased tensions between communities and police departments across the United States. In response, scholars have intensified efforts to understand the factors that shape attitudes toward the police. The current study examines individual and aggregate factors that influence satisfaction with the police. To this end, we address three research questions: (a) are there significant racial/ethnic differences in satisfaction with police; (b) do these differences persist after accounting for experiences with the police, perceptions of safety, and aggregate measures; and (c) can procedural justice help explain racial variation in attitudes toward the police? Study findings highlight the importance of perceptions of safety in explaining racial/ethnic variation in attitudes toward the police.